Towards an Ontology to Describe the Taxonomy of Common Modules in Learning Management Systems - Montenegro-Marin, Carlos Enrique; Cueva-Lovelle, Juan Manuel; Sanjuan, Oscar; Nuñez-Valdez, Edward Rolando (International Journal of Interactive Multimedia and Artificial Intelligence (IJIMAI), 2019)
This article have the objective a create ontology for "common modules in a Learning Management Systems", the steps for the build Ontology were: Determine the domain and scope of the ontology, Consider reusing existing ontology, Enumerate important terms in the ontology, Define the classes and the class hierarch, Define the properties of classes—slot and Define the facets of the slot, finally be explained how the ontology is composed.
Keywords: ontology; class; learning management systems; common modules; protégé; IJIMAI